Effect of family and patient centered empowerment program on depression, anxiety and stress in patients with obsessive-compulsive disorder and their caregivers' burden - Tahereh Heidari; Seyed-Mohammad Mousavi; Seyed-Nouraddin Mousavinasab; Hamideh AzimiLolaty (Wolters Kluwer Medknow Publications, 2020)
Background: Considering the importance of family participation in patients' treatment and the positive effects of simultaneous patient and family education, this study was conducted to determine the effect of a family and patient-oriented empowerment program on depression, anxiety, and stress in patients with Obsessive-Compulsive Disorder (OCD) and their caregivers' burden. Materials and Methods: This quasi-experimental study was conducted on 50 OCD patients along with their primary caregivers. The intervention group participated in eight sessions of training, each lasting from 60 to 90 min (twice a week), and the control group received the usual treatment. The Depression, Anxiety and Stress Scale, Maudsley's Obsessive-Compulsive Inventory, Goldberg's General Health Questionnaire, and Zarit's Burden Inventory were used to collect the data before, immediately after and 1 month after the intervention, and then the gathered data were analyzed with t-test and analysis of variance using the Statistical Package for the Social Sciences software, version 21. Results: The changes in the mean scores of depression (F2,48= 21.02, p < 0.001), anxiety (F2,48= 29.72, p < 0.001), and stress (F2,48= 16.52, p < 0.001) of the patients in the intervention group showed significant decrease over time; however, in the control group, there was no significant decrease in the mean scores of depression (F2,48= 1.69, p = 0.19), anxiety (F2,48= 0.47, p = 0.62), and stress (F2,48= 1.09, p = 0.34) over time. The changes in the caregiver's burden score in both groups indicated a significant decrease over time in the intervention group (F2,48= 24.70, p < 0.001) and the control group (F2,48= 33. 30, p < 0.001). Conclusions: The findings of this study revealed that concurrently training the patients and caregivers could reduce the negative emotions of the patients and their caregivers' burden.